Maternal Diabesity and Fetoplacental Dysfunction: Pathophysiological Pathways and Clinical Implications - Szydełko, Joanna; Szydełko-Gorzkowicz, Magdalena (Journal of Education, Health and Sport, 2026)
Background. Maternal diabesity, defined as the coexistence of obesity and diabetes during pregnancy, is an increasingly prevalent metabolic condition associated with adverse maternal, placental, and fetal outcomes. Beyond hyperglycemia, it is characterized by chronic inflammation, insulin resistance, oxidative stress, endothelial dysfunction, which impair placental development and function. The fetoplacental unit represents a critical interface through which maternal metabolic disturbances shape fetal growth and long-term health. Aim. To integrate current evidence on placental diabesity, focusing on key mechanisms linking maternal metabolic dysfunction to placental maladaptation and its clinical implications for pregnancy and offspring outcomes. Material and methods. This research was based on a literature review of PubMed and Web of Science articles published between 2010-2025. Peer-reviewed experimental, clinical and translational studies, meta-analyses were included and synthesized narratively. Description of knowledge. The available evidence indicates that maternal diabesity induces early and persistent fetoplacental dysfunction, characterized by impaired endothelial insulin signaling, reduced nitric oxide bioavailability, enhanced oxidative and inflammatory stress, mitochondrial impairment, and activation of endoplasmic reticulum stress pathways. These interconnected alterations compromise placental blood flow, nutrient transport, and metabolic adaptability, thereby increasing fetal exposure to an adverse intrauterine environment and contributing to developmental programming of metabolic and cardiovascular disease. Conclusions. Fetoplacental dysfunction is a key mechanism linking maternal diabesity to impaired fetal development and long-term offspring health. Understanding placental maladaptation in diabesity is essential for developing preventive and therapeutic strategies beyond glycaemic control to reduce intergenerational metabolic risk.